1992
DOI: 10.1007/bf02171054
|View full text |Cite
|
Sign up to set email alerts
|

Administration of milk from cows immunized with intestinal bacteria protects mice from radiation-induced lethality

Abstract: Oral administration of "immune milk", that had been obtained from cows immunized with a variety of human gut bacteria containing E. coli, S. typhimurium, S. dysenteriae and 23 others, protected AKR/J mice from the lethal effect of radiation, when immune milk was orally given to mice at 150 g kg-1 day-1 for 7 days prior to gamma-irradiation of 8 Gy. Mean survival times were 24.8 days for the group given immune milk but only 16.8 days for the group given control milk from unimmunized cows. Enterobacteriaceae wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…One explanation could be that bovine immune milk contains a low-molecular-weight factor which prevents the migration of leucocytes from the circulation to the joint, thus reducing active synovitis [55]. The specific antibacterial effect ofbovine immune milk is thought to be antibody-mediated [56,57], but judging from animal studies the promotion ofthe intestine's immunological defence mechanisms may also be important [58,59]. In our study,no clinical effect was achieved with any dietary therapy.…”
Section: Concentration Oftnf-qt and Ct-l-antitrypsin In Faecescontrasting
confidence: 73%
“…One explanation could be that bovine immune milk contains a low-molecular-weight factor which prevents the migration of leucocytes from the circulation to the joint, thus reducing active synovitis [55]. The specific antibacterial effect ofbovine immune milk is thought to be antibody-mediated [56,57], but judging from animal studies the promotion ofthe intestine's immunological defence mechanisms may also be important [58,59]. In our study,no clinical effect was achieved with any dietary therapy.…”
Section: Concentration Oftnf-qt and Ct-l-antitrypsin In Faecescontrasting
confidence: 73%
“…This kind of milk is characterized by higher amounts of immunoglobulins specific to these gut bacteria. As we previously reported, immune milk-administration protected mice from opportunistic infection induced by 5FU and irradiation [14,15]. It improved autoimmune diseases assessed by survival rate, proteinuria and anti-DNA Abs in autoimmune disease-prone mice (NZBxNZW F1 mice) [16] and it also delayed age-related impairment of T cell responses [17].…”
Section: Introductionmentioning
confidence: 83%
“…Thus, individual commensal species influence the composition of the lamina propria Th subsets that have distinct effector functions. In 1957, Stolle produced a kind of bovine milk that was termed “hyperimmunized milk” (immune milk) [14]. It was obtained from cows immunized with various human gut bacteria, including Escherichia coli , Salmonella thyphimurium , Shigella dysenteriae , Staphylococcus pyogenes , Proteus vulgaris and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG-antigen complexes are actively adsorbed and transported to dendritic cells [5]. Ishida et al [6] demonstrated that oral administration of milk IgG significantly enhanced the immunological functions of gastrointestinal associated lymphoid tissue (GALT) cells. Kobayashi et al [7] found that the level of IgA in the supernatant of Peyer's Patch cell cultures was higher in mice given cow's milk containing relatively higher IgG than in mice that ingested cow's milk with relatively lower IgG.…”
Section: Introductionmentioning
confidence: 99%